To determine which table shows that \( y = -f(x) \) results in a reflection over the x-axis, we need to understand what \( -f(x) \) means. When we take the negative of a function \( f(x) \), we're flipping the output values (i.e., the y-values) from positive to negative and vice versa.
For a reflection over the x-axis:
- If \( f(x) \) has a positive value, \( -f(x) \) will have a corresponding negative value.
- If \( f(x) \) has a negative value, \( -f(x) \) will have a corresponding positive value.
- If \( f(x) \) is zero, \( -f(x) \) will also be zero.
Now, let's examine each of the provided tables to see which one reflects this behavior:
-
Table 1: \[ \begin{array}{|c|c|} \hline x & -f(x) \ \hline 2 & 0 \ 3 & -1 \ 6 & -2 \ \hline \end{array} \]
- Here: \( f(2) = 0 \) (0 remains 0), \( f(3) = 1 \) (1 becomes -1), \( f(6) = 2 \) (2 becomes -2). This seems to reflect over the x-axis.
-
Table 2: \[ \begin{array}{|c|c|} \hline x & -f(x) \ \hline -2 & 0 \ -3 & 1 \ -6 & 2 \ \hline \end{array} \]
- Here: \( f(-2) = 0 \) (0 remains 0), \( f(-3) = -1 \) (1 becomes -1), \( f(-6) = -2 \) (2 becomes -2). This does not reflect the behavior correctly.
-
Table 3: \[ \begin{array}{|c|c|} \hline x & -f(x) \ \hline 2 & 0 \ 3 & 1 \ 6 & 2 \ \hline \end{array} \]
- Here: \( f(2) = 0 \) (0 remains 0), \( f(3) = -1 \) (1 is not matched to -1), \( f(6) = -2 \) (2 is not matched to -2). This does not reflect the behavior.
-
Table 4: \[ \begin{array}{|c|c|} \hline x & -f(x) \ \hline -2 & 0 \ -3 & -1 \ -6 & -2 \ \hline \end{array} \]
- Here: \( f(-2) = 0 \) (0 remains 0), \( f(-3) = 1 \) (1 becomes -1), \( f(-6) = 2 \) (2 becomes -2). This does not reflect the behavior correctly.
Thus, the correct table that shows \( y = -f(x) \) resulting in a reflection over the x-axis is Table 1.